The unusual broad-band X-ray spectral variability of NGC 1313 X-1 seen with XMM–Newton, Chandra, and NuSTAR. Issue 4 (26th April 2020) - Walton, D J; Pinto, C; Nowak, M; Bachetti, M; Sathyaprakash, R; Kara, E; Roberts, T P; Soria, R; Brightman, M; Canizares, C R; Earnshaw, H P; Fürst, F; et al.
ABSTRACT: We present results from the major coordinated X-ray observing programme on the ULX NGC 1313 X-1 performed in 2017, combining XMM–Newton, Chandra, and NuSTAR, focusing on the evolution of the broad-band (∼0.3–30.0 keV) continuum emission. Clear and unusual spectral variability is observed, but this is markedly suppressed above ∼10–15 keV, qualitatively similar to the ULX Holmberg IX X-1. We model the multi-epoch data with two-component accretion disc models designed to approximate super-Eddington accretion, allowing for both a black hole and a neutron star accretor. With regards to the hotter disc component, the data trace out two distinct tracks in the luminosity–temperature plane, with larger emitting radii and lower temperatures seen at higher observed fluxes. Despite this apparent anticorrelation, each of these tracks individually shows a positive luminosity–temperature relation. Both are broadly consistent with L  ∝ T 4, as expected for blackbody emission with a constant area, and also with L  ∝ T 2, as may be expected for an advection-dominated disc around a black hole. We consider a variety of possibilities for this unusual behaviour. Scenarios in which the innermost flow is suddenly blocked from view by outer regions of the super-Eddington disc/wind can explain the luminosity–temperature behaviour, but are difficult to reconcile with the lack of strong variability at higher energies, assuming this emission arises from the most compact regions. Instead, we may be seeing evidence for further radial stratification of the accretion flow than is included in the simple models considered, with a combination of winds and advection resulting in the suppressed high-energy variability.